BACKGROUND THERMAL CONTRIBUTIONS IN TESTING THE UNRUH EFFECT - Costa, S. S.; Matsas, GEA (American Physical Soc, 1995)
We consider inertial and accelerated Unruh-DeWitt detectors moving in a background thermal bath and calculate their excitation rate. It is shown that for fast moving detectors such a thermal bath does not affect substantially the excitation probability. Our results are discussed in connection with a possible proposal of testing the Unruh effect in high energy particle accelerators.